2011
DOI: 10.1039/c0cp02371j
|View full text |Cite
|
Sign up to set email alerts
|

Is the methanation reaction over Ru single crystals structure dependent?

Abstract: The influence of monoatomic steps and defects on the methanation reaction over ruthenium has been investigated. The experiments are performed on a Ru(0 1 54) ruthenium single crystal, which contains one monoatomic step atom for each 27 terrace atoms. The methanation activity is measured at one bar of hydrogen and CO in a high pressure cell, which enables simultaneous measurements of the local reactivity of the well defined single crystal surface and the global reactivity of the entire crystal and its auxiliary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
1
17
1
Order By: Relevance
“…60 Similar conclusions were derived also for reaction on Ru single crystal surfaces. 61 The apparent discrepancy with the present observations may be related to the very small particle sizes in the present study, where other particle size related effects, such as size dependent changes in the electronic properties, may also play a role. Alternatively, this may also be related to metal support interactions, which had been demonstrated for Ru on the reducible TiO 2 support, 11 while it should be absent for Ru/SiO 2 or Ru single crystal surfaces.…”
Section: Ru Particle Size / Particle Shape Effectscontrasting
confidence: 99%
“…60 Similar conclusions were derived also for reaction on Ru single crystal surfaces. 61 The apparent discrepancy with the present observations may be related to the very small particle sizes in the present study, where other particle size related effects, such as size dependent changes in the electronic properties, may also play a role. Alternatively, this may also be related to metal support interactions, which had been demonstrated for Ru on the reducible TiO 2 support, 11 while it should be absent for Ru/SiO 2 or Ru single crystal surfaces.…”
Section: Ru Particle Size / Particle Shape Effectscontrasting
confidence: 99%
“…the methanation reaction). Work by Chorkendorff and co workers showed that the activity of mass-selected supported ruthenium clusters for methanation correlates with the concentration of active sites such as step sites on the Ru surface [36,37]. Finally, the work of Quek et al [38] shows that the ability to dissociate CO is not restricted to step edges of a particular type.…”
Section: Co Activation and Oxygen Hydrogenationmentioning
confidence: 94%
“…The relevance of surface steps and defects for catalytic purposes has been elucidated by the work of Vendelbo et al, 20,21 who investigated the reactivity of the Ru(0154) surface (Ru(0001) with 4% steps) for methanation. Not only the steps proved to be of paramount importance for successful methane formation, but defects induced by sputtering readily improved the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%